English language self-efficacy in a blending learning environment / Suthagar Narasuman and Zalina Mohd Zamri - Narasuman, Suthagar; Mohd Zamri, Zalina (Universiti Teknologi MARA Cawangan Selangor, 2018)
The aim of this study was to look at the effect of blended learning (BL) on the respondents’ English as a second language (ESL) self-efficacy. The respondents in this study were subjected to a pre and post study survey on ESL self-efficacy in a BL environment. Between the surveys was an eight week period during which the respondents’ formal ESL lessons were conducted using the blended learning approach. The study utilised both quantitative and qualitative data. Data from the pre and post-test surveys were analysed to ascertain the respondents’ attitude towards blended learning and their self-efficacy in ESL. The results of this study revealed that blended learning had a positive influence on the diploma level respondents’ self-efficacy in ESL learning. They believe that blended learning had helped improve their listening skills (74.4%), speaking skills (68.3%), reading skills (92.7%), writing skills (56.1%) and grammar (59.8%).